Juvenile nasoangiofibroma: an interdisciplinary case management - Díaz Quiquia, Vasti Evelyn (2019)
Introduction: The objective is to describe the case of juvenile nasopharyngeal angiofibroma (JNA) consideredas a benign, highly vascularized nasopharyngeal tumor, currently corresponds to one of every 10,000otorhinolaryngological consultations and 0.5% of all head and neck tumors. Clinical case: It is characterizedby recurrent epistaxis and nasal obstruction. The case of a 16-year-old adolescent with recurrent epistaxis and anasal obstruction of one year of evolution is presented. CT and MRI are performed where a contrast-enhancednasopharyngeal mass is evident. Therefore, embolization is scheduled prior to surgery. Extracts angiofibromatosotumor of 8x4x2 cm, with previous tamponade. The patient is in his postoperative period evolving favorably.Conclusions: Juvenile nasoangiofibroma is the most common benign neoplasm of the nasopharynx with malignantbehavior. The prognosis is favorable in proportion to its recognition and early extirpation. Early diagnosis andmultidisciplinary management is the key to success.